Key technologies of NR multicast and broadcast services - Xiayan XU (Dianxin kexue)
Internet protocol television (IPTV), group communication and other applications are regarded as multicast/broadcast services.5G cellular mobile communication system should support the transmission of such application data efficiently.Firstly, the basic architecture of 5G multicast/broadcast system based on NR was analyzed according to the different transmission modes of multicast/broadcast application data from 5GC to UE via gNB.Then, the key technologies of 5G multicast/broadcast radio transmission were analyzed in detail from the aspects of air interface protocol stack, physical layer and higher layer protocol enhancements, service process and service continuity, etc.Finally, the evolution trends of 5G multicast/broadcast technology were prospected.